2021
DOI: 10.1007/s00267-021-01573-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Provision Ecosystem Services Associated with Land Use/Cover and Climate Variability in the Winike Watershed, Omo Gibe Basin of Ethiopia

Abstract: The provision of freshwater is essential for sustaining human life. Understanding the water provision modelling associated with the Land Use/Cover (LUC) change and climatic factors is vital for landscape water resource management. The Winike watershed is the largest tributary in the upper Omo Gibe basin of Ethiopia. This research aims to analyze the spatial and temporal change in the water yield to investigate the water yield contribution from the watershed based on the variation in input parameters. The Integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 90 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Land-use type is the key influencing node of all ESs except HQ, which reflects this situation. Extensive research has shown that reasonable human activities can improve the ecological environment (Aneseyee et al, 2022). However, in addition to human activities, ecosystem services are greatly influenced by natural factors such as climate and vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Land-use type is the key influencing node of all ESs except HQ, which reflects this situation. Extensive research has shown that reasonable human activities can improve the ecological environment (Aneseyee et al, 2022). However, in addition to human activities, ecosystem services are greatly influenced by natural factors such as climate and vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the influence of these factors exceeds the bearing capacity of the ecosystem, environmental problems such as ecological degradation will occur to different degrees. The changes in the ecosystem services in the Yellow River Basin (Henan section) were affected by the changes in the land use types, precipitation, temperature and the various human activities [ 44 , 45 ]. According to the above results, the changes in the ecosystem services in this study were closely related to the changes in the land use types.…”
Section: Discussionmentioning
confidence: 99%
“…The Budko theory underpins the InVEST model, which serves as a powerful framework for water volume simulation and testing [20]. The model employs meta-scale calculations, and the output is presented in a visualized form that directly relates to ecosystem services [21,22].…”
Section: Introductionmentioning
confidence: 99%